Evolution mechanisms of the scratch-induced elastoplastic stress fields and crack damage in γ-TiAl alloys - Zhaoqing Zhang; Kaining Shi; Yaoyao Shi; Huhu Li; Danni Lu; Yujie Kuang; Jiacheng Liu (Journal of Materials Research and Technology)
γ-TiAl alloys are extensively utilized in aero-engine turbine blades due to their exceptional physical and mechanical properties. However, the damage mechanisms during the machining of γ-TiAl alloys remain unclear, primarily due to the complexities in analyzing stress distribution and damage evolution during machining. Therefore, investigating the damage mechanisms of machining-induced, particularly the initiation and evolution of such damage, is critically important for achieving efficient and low-damage processing. In this study, scratch experiments were conducted to simulate the material removal process during grinding. The discrete wavelet transform (DWT) was applied to analyze load signals during the scratching process, enabling the precise identification of the plastic-to-brittle transition domain and the critical cutting depth for γ-TiAl alloys, and clarifying the damage mechanisms under different cutting depths. Furthermore, an analytical model of the elastoplastic stress field was established, and a system model of the crack initiation and propagation was developed by systematically analyzing the influence of the elastoplastic stress field on crack damage evolution. Detailed quantitative and visual analyses of the stress field variations, surface morphology characteristics, and crack propagation paths at the surface, shallow, and deeper layers revealed that the elastoplastic stress field model accurately reflects the stress field evolution during the scratching process of γ-TiAl alloys, and the mechanisms of crack initiation and propagation at both the surface and subsurface was elucidated and verified. These findings provide a robust theoretical foundation for the efficient and low-damage machining of γ-TiAl alloys.